Toward integrated historical climate research: the example of Atmospheric Circulation Reconstructions over the Earth. (15th January 2016) - Allan, Rob; Endfield, Georgina; Damodaran, Vinita; Adamson, George; Hannaford, Matthew; Carroll, Fiona; Macdonald, Neil; Groom, Nick; Jones, Julie; Williamson, Fiona; Hendy, Erica; Holper, Paul; et al.
Abstract : Climate change has become a key environmental narrative of the 21st century. However, emphasis on the science of climate change has overshadowed studies focusing on human interpretations of climate history, of adaptation and resilience, and of explorations of the institutions and cultural coping strategies that may have helped people adapt to climate changes in the past. Moreover, although the idea of climate change has been subject to considerable scrutiny by the physical sciences, recent climate scholarship has highlighted the need for a re‐examination of the cultural and spatial dimensions of climate, with contributions from the humanities and social sciences. Establishing a multidisciplinary dialogue and approach to climate research past, present, and future has arguably never been more important. This article outlines developments in historical climatology research and considers examples of integrated multidisciplinary approaches to climate, climatic variability, and climate change research, conducted across the physical sciences, social sciences, humanities, and the arts. We highlight the international Atmospheric Circulation Reconstructions over the Earth (ACRE) initiative as one example of such an integrated approach. Initially, ACRE began as a response from climate science to the needs of the agricultural sector in Queensland, Australia for a longer, more spatially, and temporally‐complete database of the weather. ACRE has now evolved to embrace an international group of researchers working together across disciplines to integrate their efforts into a four‐dimensional (4D) dynamical global historical climate‐quality reanalysis (reconstruction). WIREs Clim Change 2016, 7:164–174. doi: 10.1002/wcc.379 This article is categorized under: Climate, History, Society, Culture > Disciplinary Perspectives Paleoclimates and Current Trends > Modern Climate Change